Development of vocabulary learning application by using machine learning technique - Noor Mohd Ariff Brahin; Haslinah Mohd Nasir; Aiman Zakwan Jidin; Mohd Faizal Zulkifli; Tole Sutikno (Institute of Advanced Engineering and Science, 2020)
Nowadays an educational mobile application has been widely accepted and opened new windows of opportunity to explore. With its flexibility and practicality, the mobile application can promote learning through playing with an interactive environment especially to the children. This paper describes the development of mobile learning to help children above 4 years old in learning English and Arabic language in a playful and fun way. The application is developed with a combination of Android Studio and the machine learning technique, TensorFlow object detection API in order to predict the output result. Developed application namely “LearnWithIman” has successfully been implemented and the results show the prediction of application is accurate based on the captured image with the list item. The inclusion of the user database for lesson tracking and new lesson will be added for improvement in the future.